2001
DOI: 10.1016/s1074-7613(01)00210-2
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Transactivates the Human Endogenous Retrovirus HERV-K18 that Encodes a Superantigen

Abstract: Superantigens (SAgs) are proteins produced by pathogenic microbes to elicit potent, antigen-independent T cell responses that are believed to enhance the microbes' pathogenicity. Here we show that the human lymphotropic herpesvirus Epstein-Barr virus (EBV) transcriptionally activates the env gene of an endogenous retrovirus, HERV-K18, that possesses SAg activity. SAg activity was demonstrated by MHC class II dependent preferential activation of TCRVB13 T cells in response to murine B cells transfected with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
220
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 273 publications
(243 citation statements)
references
References 45 publications
5
220
1
4
Order By: Relevance
“…IL-1 and tumor necrosis factor α (TNFα) stimulate, while IFN-γ inhibits transcription of HERV-R in human vascular endothelial cells [86]. IFN-α induces expression of HERV-K18.1 env, which acting as a superantigen, causes Vβ7- [87] or Vβ13-specific T-cell expansions [88]. Steroids have long been known to induce expression and virion formation from ERV in the mouse [89].…”
Section: Immunomodulation By Ervmentioning
confidence: 99%
“…IL-1 and tumor necrosis factor α (TNFα) stimulate, while IFN-γ inhibits transcription of HERV-R in human vascular endothelial cells [86]. IFN-α induces expression of HERV-K18.1 env, which acting as a superantigen, causes Vβ7- [87] or Vβ13-specific T-cell expansions [88]. Steroids have long been known to induce expression and virion formation from ERV in the mouse [89].…”
Section: Immunomodulation By Ervmentioning
confidence: 99%
“…␥-Herpesviruses such as EBV and murine ␥-herpesvirus 68 (MHV-68) show a SAg-like activity: EBV activates a host SAg on infection (51). MHV-68 shows a V␤4-specific MHC unrestricted oligoclonal CD8 T cell stimulation (52).…”
Section: Different Strategies Leading To Similar Outcomes: Mmtv Vs Ebvmentioning
confidence: 99%
“…Retroviral superantigens were first depicted in the B-type virus group in mouse mammary tumor viruses and are found in both infectious mouse mammary tumor viruses and endogenous proviruses (14,18,39,63). It has been previously shown that the env gene of HERV-K18, a defective human endogenous provirus located on chromosome 1, encodes a superantigen activity (51,52). The HERV-K family is closely related to the B-type retroviruses based on amino acid similarity in the reverse transcriptase gene (48).…”
mentioning
confidence: 99%